(untitled) (Global Journal of Medical Research, 2023)
Background: In today’s dynamic health systems, technology plays an essential role in education and nursing practice. Therefore, it is necessary to study the changing role of nurses and highlight the need for appropriate information technology educational programs to integrate with the ever-increasing pace of technology. Nursing informatics helps improve vital nursing processes, such as documentation, which is a critical aspect of the profession and essential for effective patient care. Before electronic health records, nurses recorded patient information on charts, which could easily be mismanaged. Today, nursing informatics simplifies documentation and automates the transmission of patient data via connected devices to provide access for nurses, physicians, and patients.